Correlation of Pap smear and visual inspection with acetic acid for screening of premalignant and malignant lesion of cervix - Singh, Anshu; Singh, Kalpana; Agarwal, Nisha Rani (International Journal of Research in Medical Sciences, 2017)
Background: Cervical cancer still remains a leading cause of morbidity and mortality among women worldwide. Despite attempts to increase screening over the past several decades, incidence and mortality rates of cancer cervix have not shown substantial reduction. The conventional method of screening by cervical cytology/pap smear has failed to reduce the disease burden due to lack of patient compliance for repeated testing and a relatively sophisticated infrastructure. Therefore, alternative methods such as visual inspection after application of acetic acid (VIA), visual inspection with Lugol's Iodine (VILI) and human papillomavirus (HPV) DNA testing have been developed. The aim of present study was to compare Pap smear and VIA and evaluate their usefulness as tools for screening of premalignant and malignant lesions of cervix. Methods: This was a crossectional study over 5 months from 1 Jan 2015 to 31 may 2015 in which 212 patients attending the obstetrics and gynecology department, BHU were enrolled. Pap smear was taken followed by VIA. Pap smears were sent to pathology department, BHU where they were reported as per Bethesda System, 2001. Cervical biopsies were done in positive cases. Data obtained and statistically analyzed. Results: The present study was conducted over a period of 6 months among 212 patients age of 18-60 years screened. Positive results obtained from cytology were 26, VIA was positive in 28 women. Cervical biopsy was done in 34 women who had positive results by either test. Histology in 31 cases was suggestive of cervical intraepithelial carcinoma (CIN). Conclusions: VIA, though less specific has comparable sensitivity to Pap smear and may be used as a primary screening tool for cervical cancer. In combination both the tests have a higher predictive accuracy.